3,3′-diindolylmethane inhibits LPS-induced human chondrocytes apoptosis and extracellular matrix degradation by activating PI3K-Akt-mTOR-mediated autophagy - Tang, Hao; Qin, Kunpeng; Wang, Anquan; Li, Shuang; Fang, Sheng; Gao, Weilu; Lu, Ming; Huang, Wei; Zhang, Hui; Yin, Zongsheng (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is a chronic degenerative joint disease characterized by articular cartilage destruction. The pathological mechanisms are complex; in particular, inflammation, autophagy, and apoptosis are often involved. 3,3-Diindolylmethane (DIM), a phytoconstituent extracted from cruciferous vegetables, has various effects such as anti-inflammatory, antioxidant and anti-apoptotic. However, the effects of DIM on osteoarthritic chondrocytes remain undetermined. In this study, we simulated a lipopolysaccharide (LPS)-induced osteoarthritis model in human primary chondrocytes. We found that LPS stimulation significantly inhibited autophagy, induced chondrocyte apoptosis and extracellular matrix (ECM) degradation, which could be ameliorated by DIM. DIM inhibited the expression of a disintegrin and metalloproteinase with thrombospondin motif 5 (ADAMTS-5), matrix metalloproteinase 13 (MMP13), cleaved caspase-3, Bax, and p62, and increased the expression level of collagen II, aggrecan, Bcl-2, light chain 3 Ⅱ (LC3 Ⅱ), and beclin-1. Mechanistic studies showed that DIM increased chondrocyte autophagy levels by inhibiting the activation of PI3K/AKT/mTOR pathway. In mice destabilization of the medial meniscus (DMM) model, immunohistochemical analysis showed that DIM inhibited the expression of p-PI3K and cleaved caspase-3, increased the expression of LC3 Ⅱ. Furthermore, DIM relieved joint cartilage degeneration. In conclusion, our findings demonstrate for the first time that DIM inhibits LPS-induced chondrocyte apoptosis and ECM degradation by regulating the PI3K/AKT/mTOR-autophagy axis and delays OA progression in vivo.